The Role of the Creative Economy in Enhancing Indonesia's Competitiveness in the Post-Pandemic Era - Haryati, Haryati (Fakultas Ekonomi Universitas Gresik, 2024)
The creative economy has become a crucial pillar in Indonesia's recovery and competitiveness after the COVID-19 pandemic, driven by the increasing contribution of the culinary, fashion, and digital applications subsectors to the national economy. This study aims to deeply analyze the role of the creative economy in strengthening Indonesia's competitiveness in the post-pandemic era by highlighting innovation, digitalization, and cross-sector collaboration strategies. The research method employed a descriptive qualitative approach with purposive sampling of 20 key informants, including creative entrepreneurs, local governments, associations, and academics. Data were collected through in-depth interviews, limited observations, and documentation studies, then analyzed using thematic analysis with source triangulation to ensure the validity of the findings. The results indicate that digital transformation expands market reach, improves operational efficiency, and creates new export opportunities, although significant challenges remain, such as limited capital, low digital literacy, and uneven infrastructure. The findings also emphasize the importance of an integrated, innovation-based strategy, government policy support, and a strengthened collaborative ecosystem to make the creative economy a driver of sustainable development. This study provides theoretical contributions to enrich the creative economy literature while offering practical recommendations for policymakers and creative entrepreneurs.